Permainan Pretend Play menggunakan Gadget dalam Mengembangkan Aspek Kognitif dan Budaya Anak Usia Dini - Kusna, Siti Labiba (Indonesian Journal of Islamic Early Childhood Education, 2018)
Gadgets have developed rapidly in the globalization era and always make a renewal to attract the users. The development of gadgets certainly has an impact on the children development that since before birth have been introduced to gadgets, of course different from the time our parents did not know or know gadgets in a limited way. Gadgets are not to be avoided, but have to be optimized for the benefit of children towards a positive direction and reduce the negative impact that will affect children, because life is inseparable from the gadget. PAUD institutions can use the pretend play game by using gadgets based on existing research results, pretend play has a positive impact on the development of children's cognitive aspects and children's culture